Radioisotopic evaluation of reparative osteogenesis in various forms of osteomyelitis of the mandible - Komskyi , M.P.; Romanenko, Ye.G; Lisova , I.G.; Titov , G.I.; Trushenko, O.S.; Lavreniuk , Ya.V. (Medicni Perspektivi, 2023)
The aim of this work is the rationale for using radiological method of examination in diagnosing and monitoring the mandibular osteomyelitis treatment. A total of 60 patients with traumatic (first group) and odontogenic (second group) mandibular osteomyelitis were examined. Among them, there were 24 (40%) males and 36 (60%) females aged between 20 and 45 years. The patients received intravenous injection of Technefor (99MTc) with the radiation activity of 300-400 megabecquerel 3-4 hours before scintigraphy. The mandible radiopharmaceutical uptake was measured using a computerized gamma camera. The level of 99MTc accumulation in the bone tissue was quantified by gamma-radiation. A patient was examined on the day of hospital admission and on day 14 after surgical treatment of osteomyelitis of the mandible. Our studies have shown that all forms of traumatic and odontogenic osteomyelitis are accompanied by significant changes in 99MTc uptake in the mandible, however, both 99MTc uptake and its decrease after surgical treatment were most obvious in odontogenic osteomyelitis. The increase in 99MTc uptake in traumatic mandibular osteomyelitis was 38,1% (up to 1669,9 gamma-radiation pulses), 140,9% (up to 2913,7 gamma-radiation pulses) and 129% (up to 2772,7 gamma-radiation pulses) in the acute, subacute and chronic stages of the disease, respectively. The increase in 99MTc uptake in odontogenic mandibular osteomyelitis was 160,0% (up to 3144,1 gamma-radiation pulses), 218,1% (up to 3846,6 gamma-radiation pulses) and 275,2% (up to 4537,6 gamma-radiation pulses) in the acute, subacute and chronic stages of the disease, respectively. The increase in 99MTc uptake was due to blood flow enhancement, metabolic disorders, activation of osteoblast and osteoclasts in the bone tissue. The decrease in 99MTc uptake after the treatment indicated the positive response to treatment. Scintigraphic examination was more sensitive and specific in comparison to X-ray diagnostics of mandibular ostemyelitis. The sensitivity of scintigraphic findings ranged from 60.0% to 100%, and the specificity was 100% at different stages of ostemyelitis.